Early History of Educational Dictionaries and the First Bilingual Dictionaries (Journal of Pedagogical Inventions and Practices, 2023)
It is based on the fact that the bilingual dictionary, compiled in order to serve the correct understanding, originated in the form of manuals – educational dictionaries. In particular, the bilingual glossaries found in the temple library in Nippur, dating back to four millennia BC, intended for communication between two completely different tribes -Sumerian and Akkadian Semites who lived in Ancient Mesopotamia – were the first appearance of modern bilingual educational dictionaries.